Analisis Pengendalian Kualitas Produk Furniture dengan Metode SPC dan FMEA pada PT. Multi Manao Indonesia - Fadhil, Moch Nur; Khoiroh, Siti Muhimatul (SURYA TEKNIKA, 2025)
This research addresses the importance of quality control in the furniture industry, particularly in maintaining product consistency and reducing defects. PT. Multi Manao Indonesia, a furniture manufacturing company, faces challenges in quality consistency, especially in the Setting Warna section. This study aims to analyze quality control at PT. Multi Manao Indonesia using the Statistical Process Control (SPC) method, focusing on the Aaron Side Chair product, and further identifying defect causes through Failure Mode and Effect Analysis (FMEA). SPC is used to monitor production process stability and detect variations affecting quality, while FMEA is applied to assess and prioritize potential failure modes. The findings are expected to support the company in improving process control, reducing defects, and enhancing production efficiency.